Alkali-free glass with low reheat shrinkage rate as well as preparation method and application of alkali-free glass

By using alkali-free glass with a specific ratio and low reheat shrinkage rate in OLED manufacturing, the problem of irreversible shrinkage of the glass substrate caused by high-temperature heat treatment is solved, achieving both high strain point and low reheat shrinkage rate, ensuring The quality and performance of OLED panels.

CN119330583APending Publication Date: 2025-01-21CHONGQING AUREAVIA HI TECH GLASS CO LTD

Patent Information

Application Number
CN202411412869.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing glass substrates are irreversible shrinkage caused by high-temperature heat treatment during the OLED manufacturing process, resulting in a shift in pixel spot positions, which may cause light leakage, black spots and other display defects, seriously affecting the quality of the panel.

Method used

A kind of low reheat shrinkage alkali-free glass is used. Its raw materials include SiO2, Al2O3, B2O3, SrO, CaO, MgO, BaO and SnO. Through specific ratios and processes, it is prepared with high strain point and low softening point. , high UV transmittance and low reheat shrinkage glass.

Benefits of technology

Under the conventional annealing conditions, the heating contraction rate of the glass is reduced to less than 35ppm, and at the same time, the strain point to 707 ° C is increased, which meets the requirements of the low heat contraction rate of the polysilicon process. Size stability and display performance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses alkali-free glass with low reheat shrinkage rate as well as a preparation method and application thereof, and the glass is prepared from the following raw materials in percentage by mass: 60 to 65 percent of SiO2, 17 to 21 percent of Al2O3, 0 to 2 percent of B2O3, 4 to 8 percent of SrO, 3 to 5 percent of CaO, 4 to 7 percent of MgO, 0 to 3 percent of BaO and 0 to 2 percent of SnO. The alkali-free glass which is high in strain point, low in softening point and high in ultraviolet transmittance and meets the requirement of a polycrystalline silicon process is prepared by adopting an overflow down-draw method process under a conventional annealing condition according to a raw material ratio, on one hand, by increasing the content of SiO2, the strain point of the glass is increased, and the reheat shrinkage rate is reduced at the same time; on the other hand, BaO is introduced to regulate the density of the glass and improve the strain point temperature of the glass, the reheat shrinkage rate (600 DEG C / 1h) of the prepared alkali-free glass is below 35ppm, the strain point reaches above 707 DEG C, the softening point temperature is about 820 DEG C, the thermal expansion coefficient is 3.4 * 10 <-6 >-4.0 * 10 <-6 > / DEG C, the density is 2.52-2.57 g / cm < 3 >, the hardness is 685-712kgf / mm < 2 >, and the transmittance reaches above 74% when the visible light wavelength lambda is 308nm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional materials and relates to glass materials, in particular to an alkali-free glass with low reheat shrinkage and a preparation method and application thereof. Background Art

[0002] Displays are an important bridge for communication between people and machines, and are also a key platform for information exchange. Every leap in display technology not only brings a shocking visual experience to viewers, but also profoundly promotes the upgrading of the industry and the transformation of lifestyles. OLED screens, with their outstanding features such as lightness, fast response, wide viewing angle, low power consumption, wide color gamut, and support for flexible and transparent displays, perfectly meet the growing demand for human-computer interaction in new technologies such as 5G communications, artificial intelligence, augmented reality / virtual reality (AR / VR), and have become a popular choice for current technological development. Glass materials, with their excellent light transmittance, flat surface, heat resistance, electrical insulation, corrosion resistance, high strength and sealing, play an irreplaceable role in circuit construction and manufacturing processes, especially as the core substrate of flat panel display technology, which is essential for the manufacture of modern display devices.

[0003] Active matrix organic light emitting diode (AMOLED) is a new technology in the field of flat panel display. Its significant advantages are that it can display a richer color range, provide higher image contrast, reduce energy consumption, and has the ability to achieve screen flexibility. However, among the active matrix driving technologies of AMOLED, LTPS (low temperature polycrystalline silicon)-TFT (thin film transistor) technology is particularly eye-catching. As a current-driven element, the efficient operation of LTPS-TFT requires a larger number of TFT elements and higher driving current support. Compared with traditional amorphous silicon a-Si-TFT, LTPS-TFT has shown many advantages: it has a higher electron mobility (≈100cm 2 / V·s), which means faster signal transmission speed; at the same time, its low cut-off current helps to improve energy efficiency; in addition, LTPS-TFT also supports higher resolution, faster response speed, higher aperture ratio and higher integration. These characteristics together bring more outstanding performance and visual experience to AMOLED display technology.

[0004] The LTPS-TFT process uses advanced technologies such as laser annealing and solid phase crystallization to create LTPS-TFTs on glass substrates with electron mobility far exceeding that of a-Si-TFTs (two orders of magnitude higher), significantly improving pixel writing capabilities and making it possible to build integrated circuit systems on glass. However, during the OLED manufacturing process, especially during TFT photoetching and LTPS low-temperature polysilicon processing, the glass substrate must withstand high-temperature heating of 450 to 600°C. During this process, the glass substrate will undergo significant irreversible shrinkage due to heat treatment, resulting in pixel position shifts, which may cause display defects such as light leakage and black spots, seriously affecting the quality of the panel. As display technology develops towards high resolution, it becomes particularly critical to control the reheating linear shrinkage rate of the glass substrate.

[0005] The substrate glass that meets the OLED panel manufacturing process generally needs to meet the following important performance indicators.

[0006] (1) No alkali metal ions: During the manufacturing process of OLED substrate glass, it is crucial to control its chemical composition, especially to ensure that the content of alkali metal ions is strictly limited to less than 0.1%. This is because in the production process of OLED, the substrate glass needs to undergo high-temperature treatment at about 600°C. In such a high-temperature environment, the diffusion rate of alkali metal ions will be significantly accelerated, and they may penetrate into the thin-film transistor (TFT) and damage the circuit structure. This damage will not only affect the normal operation of the circuit, but also greatly shorten the overall service life of the OLED panel.

[0007] (2) Low reheat shrinkage; reheat shrinkage refers to the phenomenon that when the glass is reheated to near the glass transition temperature (Tg), the glass structure relaxes and the macroscopic size decreases. In the TFT photoetching process and the LTPS low-temperature polysilicon processing stage in the OLED manufacturing process, the glass substrate will be subjected to high-temperature treatment of 450°C to 600°C. Within this temperature range, if the reheat shrinkage of the glass substrate is significant, it will cause the substrate size to not match the expectation, and then cause the pixel misalignment, forming bad pixels on the display, and ultimately reducing the yield of the OLED panel. Therefore, in order to maintain high-precision pattern alignment and reduce quality problems caused by dimensional changes, the OLED substrate glass should have a low reheat shrinkage rate, thereby effectively avoiding the dimensional change effect caused by thermal relaxation.

[0008] (3) Low thermal expansion; the thermal expansion coefficient of the glass substrate is (32-38)×10 -7The matching between α-Si and K is crucial. In the process of converting amorphous silicon (α-Si) into polycrystalline silicon (p-Si) through the low-temperature polysilicon (LTPS) process, if the thermal expansion coefficients of the glass substrate and p-Si do not match, then as the temperature changes, the difference in volume change between the two will cause stress on the surface of the glass substrate, which may cause cracking, which will have an adverse effect on the overall quality and yield of the product. Therefore, in order to maintain the dimensional stability of the glass substrate during temperature changes, the glass substrate needs to have a low and stable thermal expansion coefficient to ensure a good match with p-Si, thereby avoiding problems such as stress cracking.

[0009] (4) High heat resistance: For OLED substrate glass, high heat resistance is an important indicator, which requires the glass to have a higher strain point (Tst). The strain point is the temperature point at which the glass changes from an elastic state to a plastic state. When the temperature is lower than this strain point, the glass maintains its rigid state and is not prone to permanent deformation or residual stress due to external thermal stress. Therefore, by increasing the strain point temperature of the OLED substrate glass, it is possible to more effectively resist the thermal deformation and thermal shrinkage problems caused by high-temperature heat treatment during the manufacturing process, thereby ensuring the dimensional stability and shape accuracy of the glass substrate during the manufacturing process.

[0010] (5) Low density: In the process of manufacturing large-size display panels, in order to reduce the overall weight and improve portability and installation efficiency, the design of glass substrates is moving towards lightweight. Specifically, this requires that the density of the glass substrate must be controlled at 2.6g / cm 3 The following is to achieve a lighter structure to meet the demand for lightweight materials for large-size display panels.

[0011] (6) High UV transmittance: The high ultraviolet (UV) transmittance of the substrate glass and its uniformity are crucial for the TFT and control circuit peeling step in the flexible OLED manufacturing process. This unique UV peeling process requires that the ultraviolet light can effectively penetrate the glass carrier so that the film layer can be accurately peeled off the carrier. In order to achieve efficient peeling, the substrate glass must have a high transmittance for ultraviolet light of a specific wavelength (such as 308nm), and the transmittance is usually required to be no less than 70%. Such a design can ensure that the ultraviolet light acts evenly and fully on the film layer, improve the accuracy and yield of the peeling, and thus optimize the overall manufacturing effect of the flexible OLED.

[0012] On the basis of ensuring that the glass substrate meets all the aforementioned key performance indicators, the clarification and homogenization stage in its manufacturing process also has an important impact on the quality of the final product. This stage is directly related to whether the finished glass will contain defects such as bubbles, streaks, and stones, which will seriously affect the performance and reliability of the OLED display panel. In order to obtain high-quality OLED glass substrates, the technology currently commonly used in the industry is the overflow down-pull method. This method helps to reduce or eliminate the above defects by precisely controlling the flow and cooling process of the glass liquid, thereby improving the overall quality of the glass substrate.

[0013] Compared with the traditional float process, the overflow down-draw method exhibits several significant advantages: First, during the production process, the outer surface of the glass sheet can remain in a non-contact state with any object, which greatly reduces the influence of external forces during the forming process, thereby giving the glass sheet a higher degree of flatness and smoothness. Secondly, the thinning area of ​​this method is designed to be more compact, making it possible to manufacture thinner glass sheets and making the operation easier. Furthermore, by using a pair of rollers to pull the glass ribbon, it not only improves the pulling efficiency but also ensures the stability of the glass ribbon during transmission. In addition, the overflow down-draw method also allows the glass ribbon to be heated and cooled on both sides. This double-sided temperature control method makes it easier to accurately adjust the temperature of the glass ribbon, thereby further improving the quality and consistency of the product.

[0014] The overflow down-draw method is an advanced glass manufacturing process. It first mixes a variety of raw materials in precise proportions, and then the mixture is sent to a pool furnace for high-temperature melting and converted into molten glass. The molten glass then flows through a platinum channel, which includes a clarification section and a homogenization section to eliminate visible bubbles and inhomogeneities in the molten glass and make its composition more uniform. Then, the molten glass flows horizontally into the overflow brick through a special L-shaped platinum pipe. On the upper part of the overflow brick, a collection tank (overflow tank) is designed to temporarily store the incoming molten glass. When the molten glass in the overflow tank accumulates to a certain amount, it will overflow from the edges of both sides of the top of the overflow tank under the action of gravity. The overflowed molten glass then flows slowly downward along the outer surface of the overflow brick to form two parallel glass ribbons. As the flow proceeds, the two glass ribbons gradually approach each other under the overflow brick and finally combine together to form a complete, high-quality glass plate. This unique process not only ensures the flatness and smoothness of the glass plate, but also makes it possible to manufacture thinner and more uniform glass plates.

[0015] CN110357420A discloses a method for preparing electronic substrate glass with low heat shrinkage, wherein the heat shrinkage of the prepared float alkali-free aluminum borosilicate glass is less than 10ppm through a six-step cooling annealing method; CN112777923A discloses a TFT substrate glass annealing process, wherein the reheat shrinkage of the TFT substrate glass for OLED display is 5-8ppm through a three-stage method of cooling annealing in a heat preservation stage, a slow cooling stage and a fast cooling stage, and the reheat shrinkage of the TFT substrate glass for LCD display is 24-45ppm; CN116282902A discloses an alkali-free substrate glass, wherein the strain point temperature is ≥720℃, the reheat shrinkage at 600℃ for 10min is less than 40ppm, the transmittance at a wavelength of 308nm is >70%, and the density is <2.62g / cm 3 At present, the existing patents mainly reduce the reheat shrinkage rate of the substrate glass by changing the glass cooling annealing process, but the glass formula alone cannot meet the requirements of the LTPS process for glass dimensional stability at 600°C.

[0016] Therefore, it is urgent to develop an alkali-free glass that meets the requirements of high strain point, low softening point, high UV transmittance, and low reheat shrinkage of the polysilicon process. Summary of the invention

[0017] In view of the shortcomings of the prior art, the purpose of the present invention is to provide an alkali-free glass with high strain point, low softening point, high UV transmittance and low reheat shrinkage that meets the requirements of polysilicon process, as well as a preparation method and application thereof, so as to increase the strain point of the glass and reduce the reheat shrinkage.

[0018] In order to achieve the above object, the present invention adopts the following technical solutions:

[0019] The invention discloses an alkali-free glass with low reheat shrinkage. The raw materials include, by mass percentage, 60-65% SiO2, 17-21% Al2O3, 0-2% B2O3, 4-8% SrO, 3-5% CaO, 4-7% MgO, 0-3% BaO and 0-2% SnO.

[0020] The present invention also has the following technical features:

[0021] Preferably, the mass percentage of SiO2+Al2O3 in the raw material components is 81% to 86%.

[0022] Preferably, the mass percentage of B2O3 in the raw material components is 1% to 2%.

[0023] Preferably, the mass percentage of BaO is 0.5-1.5%.

[0024] The present invention also protects a method for preparing the low reheat shrinkage alkali-free glass as described above, comprising the following steps: weighing raw materials according to a ratio and mixing them evenly, keeping them warm at 800°C for 2 hours, putting them into a high-temperature furnace at 1600°C, heating them to 1600-1640°C, keeping them warm for 2-4 hours and then taking them out, then pouring the molten glass into a preheated stainless steel mold for rapid molding, annealing at 800°C for 2 hours, and then naturally cooling them in the furnace to obtain the alkali-free glass.

[0025] The invention also protects the application of low reheat shrinkage alkali-free glass in substrate glass for low-temperature polysilicon process.

[0026] Compared with the prior art, the present invention has the following technical effects:

[0027] The present invention provides a low reheat shrinkage alkali-free glass having high strain point, low softening point, high ultraviolet transmittance and meeting the requirements of polysilicon process under conventional annealing conditions. The reheat shrinkage (600°C / 1h) is below 35ppm, while the strain point reaches above 707°C, the softening point temperature is around 820°C, and the thermal expansion coefficient is 3.4×10 -6 ~4.0×10 -6 / ℃, density is 2.52~2.57g / cm 3 , hardness is 685~712kgf / mm 2 , the transmittance reaches more than 74% at the visible light wavelength λ=308nm;

[0028] The present invention increases the content of SiO2 on the one hand, thereby increasing the strain point of the glass and reducing the reheat shrinkage rate. On the other hand, BaO is introduced to adjust the density of the glass and increase the strain point temperature of the glass, thereby increasing the strain point of the glass and reducing the reheat shrinkage rate. DETAILED DESCRIPTION

[0029] The specific contents of the present invention are further explained in detail below in conjunction with embodiments.

[0030] Among the raw materials for preparing the low reheat shrinkage alkali-free glass of the present invention, SiO2, Al2O3, B2O3, MgO, CaO, SrO, BaO and SnO are introduced from quartz sand, alumina, boric acid, light magnesium oxide, calcium carbonate, strontium carbonate, barium carbonate and stannous oxide respectively.

[0031] Example 1

[0032] This embodiment provides a method for preparing alkali-free glass suitable for overflow down-draw process, comprising the following steps:

[0033] According to the mass percentage of each oxide, SiO2 64%, Al2O3 18%, B2O3 1.2%, SrO 6%, CaO4.5%, MgO 5.5%, BaO 0% and SnO 0.8%, the mass fraction of the batch material is calculated and about 500g of the batch material is weighed, and put into a mixing granulator for mixing and then made into uniform particles. 100g of the prepared uniform particles are weighed and poured into a quartz crucible and kept at 800℃ for 2 hours, melted at 1640℃ and kept warm for 4h, and then the molten glass liquid is poured into a preheated stainless steel mold for rapid molding, annealed at 800℃ for 2h, and then naturally cooled with the furnace to eliminate the stress in the glass, and finally a low reheat shrinkage alkali-free glass sample is obtained.

[0034] Example 2

[0035] According to the mass percentage of each oxide, SiO2 65%, Al2O3 15%, B2O3 1.2%, SrO 6%, CaO4.5%, MgO 5.5%, BaO 0% and SnO 0.8%, the mass fraction of the batch material is calculated and about 500g of the batch material is weighed, and put into a mixing granulator for mixing and then made into uniform particles. 100g of the prepared uniform particles are weighed and poured into a quartz crucible and kept at 800℃ for 2 hours, melted at 1600℃ and kept for 3h, and then the molten glass liquid is poured into a preheated stainless steel mold for rapid molding, annealed at 800℃ for 2h, and then naturally cooled with the furnace to eliminate the stress in the glass, and finally a low reheat shrinkage alkali-free glass sample is obtained.

[0036] Example 3

[0037] According to the mass percentage of each oxide, SiO2 64%, Al2O3 18%, B2O3 1.2%, SrO 6%, CaO4.5%, MgO 5.5%, BaO 0.5% and SnO 0.8%, the mass fraction of the batch material is calculated and about 500g of the batch material is weighed, and put into a mixing granulator for mixing and then made into uniform particles. 100g of the prepared uniform particles are weighed and poured into a quartz crucible and kept at 800℃ for 2 hours, melted at 1620℃ and kept warm for 2h, and then the molten glass liquid is poured into a preheated stainless steel mold for rapid molding, annealed at 800℃ for 2h, and then naturally cooled with the furnace to eliminate the stress in the glass, and finally a low reheat shrinkage alkali-free glass sample is obtained.

[0038] Example 4

[0039] Example 4 is basically the same as Example 1, except that the mass percentages of the raw material oxides are SiO2 64%, Al2O3 18%, B2O3 1.2%, SrO 6%, CaO 4.5%, MgO 5.5%, BaO 1.5% and SnO 0.8%.

[0040] Example 5

[0041] Example 5 is substantially the same as Example 1, except that the mass percentages of the oxides in the raw materials are SiO2 61%, Al2O3 21%, B2O3 1.2%, SrO 6%, CaO 4.5%, MgO 5.5%, BaO 0% and SnO 0.8%.

[0042] Example 6

[0043] Example 6 is basically the same as Example 1, except that the mass percentages of the oxides in the raw materials are SiO2 60%, Al2O3 18%, B2O3 2%, SrO 8%, CaO 3%, MgO 4%, BaO 3% and SnO 2%.

[0044] Example 7

[0045] Example 7 is basically the same as Example 1, except that the mass percentages of the oxides in the raw materials are SiO2 60%, Al2O3 20%, B2O3 0%, SrO 4%, CaO 5%, MgO 7%, BaO 1% and SnO 2%.

[0046] Reheating shrinkage test method: Use a vernier caliper to measure the initial length L of the glass sample, place the sample to be tested steadily on the supporting quartz rod of the expansion instrument, and perform zero calibration. Start from room temperature and heat to 600℃ at a heating rate of 5℃ / min, keep warm for 1h, then cool to 100℃ at a cooling rate of 2℃ / min, and then cool to room temperature with the furnace. Its length shrinks relative to that before heating, and the shrinkage ΔL in the length direction of the glass is read using a thermal expansion instrument. The ratio of the shrinkage to the original length is the measured reheating linear shrinkage of the glass sample. In order to reduce the measurement error, each sample is measured at least twice.

[0047] Table 1 shows the composition and properties of the alkali-free glass of Examples 1-5:

[0048] Table 1 shows the composition and properties of the alkali-free glass of Examples 1-5

[0049] Composition (wt%) Example 1 Example 2 Example 3 Example 4 Example 5 <![CDATA[SiO2]]> 64 65 64 64 61 <![CDATA[Al2O3]]> 18 17 18 18 21 <![CDATA[B2O3]]> 1.2 1.2 1.2 1.2 1.2 SrO 6 6 6 6 6 CaO 4.5 4.5 4.5 4.5 4.5 MgO 5.5 5.5 5.5 5.5 5.5 SnO 0.8 0.8 0.8 0.8 0.8 BaO 0 0 0.5 1.5 0 <![CDATA[Density (g / cm 3 )]]> 2.5389 2.5694 2.5289 2.5691 2.5679 <![CDATA[Hardness (kgf / mm 2 )]]> 712 723 691 685 701 Transmittance (308nm) 77 77 75 74 78 <![CDATA[CTE,50-300℃(×10 -6 )]]> 3.58 3.47 3.85 3.83 3.94 Strain point(℃) 709 711 721 724 707 Softening point(℃) 821 824 834 848 818 Reheat shrinkage (ppm) 28 27 30 32 35

[0050] As shown in Table 1, the reheat shrinkage (600°C / 1h) of the alkali-free glass prepared in Examples 1 to 5 is below 35 ppm, and the glass has a relatively high strain point, reaching above 707°C, a softening point temperature of about 820°C, and a thermal expansion coefficient of 3.4×10 -6 ~4.0×10 -6 / ℃, density is 2.52~2.57g / cm 3 , hardness is 685~712kgf / mm 2 , the transmittance reaches more than 74% at the visible light wavelength λ=308nm.

[0051] The above embodiments are only examples for clear explanation, and are not intended to limit the implementation methods. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here, so the obvious changes or modifications derived are still within the protection scope of the invention.

Claims

1. A low reheat shrinkage alkali-free glass, characterized in that: The raw materials include, by mass percentage, 60-65% of SiO2, 17-21% of Al2O3, 0-2% of B2O3, 4-8% of SrO, 3-5% of CaO, 4-7% of MgO, 0-3% of BaO and 0-2% of SnO.

2. The low reheat shrinkage alkali-free glass according to claim 1, characterized in that: The mass percentage of SiO2+Al2O3 in the raw material components is 81% to 86%.

3. The low reheat shrinkage alkali-free glass according to claim 1, characterized in that: The mass percentage of B2O3 in the raw material components is 1% to 2%.

4. The low reheat shrinkage alkali-free glass according to claim 1, characterized in that: The mass percentage of BaO in the raw material components is 0.5-1.5%.

5. A method for preparing alkali-free glass with low reheat shrinkage as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: The raw materials are weighed according to the ratio and mixed evenly, then kept at 800°C for 2 hours, put into a high-temperature furnace at 1600°C, heated to 1600-1640°C, kept for 2-4 hours and then taken out, then the molten glass liquid is poured into a preheated stainless steel mold for rapid molding, annealed at 800°C for 2 hours, and then naturally cooled in the furnace to obtain the alkali-free glass.

6. Use of the low reheat shrinkage alkali-free glass according to any one of claims 1 to 4 in substrate glass for low-temperature polysilicon process.

Citation Information

Patent Citations

  • Preparation method for electronic glass substrate with low thermal shrinkage

    CN110357420A

  • TFT substrate glass annealing process and TFT substrate glass prepared by adopting same

    CN112777923A

  • Alkali-free substrate glass

    CN116282902A

Cited By

  • High-strain-point low-shrinkage alkali-free substrate glass and preparation method thereof

    CN122380653A